DESTRUKTIF BATIK: PERANCANGAN MOTIF BATIK DENGAN VISUAL DESTRUKTIF (NEGATIF FILM) DAN GAYA SUREALISME PADA PRODUK ART WEAR - Muchamad Bagus Iman; Andri Nur Cahyo; Amin Sulistiyowati (Canthing, 2024)
As time goes by, many things are influenced, one of which is art. However, on the other hand, traditional arts in each region, especially in the field of art, have not been influenced by developments over time as significantly as Batik art in Indonesia, which has only been influenced by the materials and techniques for making it. Based on this, a design concept emerged for motifs, techniques and clothing applications that were newer and less monotonous. And these three things influence the design elements, namely shape, color and material in the components used. In this design the author wants to present a new batik motif with a new color technique and apply it to new clothing. By considering the aesthetic aspects of design, function and also the psychology of the user. The method used in this design is combining batik techniques with Surrealism visuals on batik motifs and using negative film coloring techniques which will be applied to Art Wear clothing. The aim of this design is to create batik motifs with destructive visuals (film negatives) with a surrealist style in Art Wear products. Keywords: Art wear, Batik, Destructive, Surreal